Application of the Sufficiency Economy Philosophy for Work and Integration of Life and Work Affecting the Career Success of Commercial Bank Employees in Northeastern Thailand - Pongpan, Srimuang; Sarayut, Phorncharoen; Dusit, Jaksil (INTI International University, 2024)
This research aimed to study the application of the sufficiency economy philosophy in the workplace and the integration of life and work, and how they affect the career success of commercial bank employees in northeastern Thailand. The population consisted of commercial bank employees. The sample included 383 commercial bank employees, selected using stratified random sampling based on the population proportion in each province of northeastern Thailand. A questionnaire was used as the research tool. Statistics for data analysis included percentage, mean, standard deviation, and multiple regression. The results indicated that the application of the sufficiency economy philosophy at work, particularly in the aspects of reasonableness, knowledge, and moderation, as well as the integration of life and work in terms of readiness to always work, significantly influenced the career success of commercial bank employees in northeastern Thailand. Additionally, the integration of life and work, specifically in the area of work-time flexibility, also had a notable impact on the career success of these employees.